2016
DOI: 10.5606/kbbihtisas.2016.32815
|View full text |Cite
|
Sign up to set email alerts
|

Adenoidectomy: current approaches and review of the literature

Abstract: Adenoid is a secondary lymphoid organ located in the nasopharynx. Due to its location, it plays an important role in the host defense of the upper respiratory tract. Immunoglobulin G3 and immunoglobulin A1 antibodies are prevalent antibodies in the adenoid tissue. Adenoidal hypertrophy is a common condition in children causing symptoms such as mouth breathing, nasal discharge, snoring, sleep apnea, and hyponasal speech. It also plays a role in the pathogenesis of rhinosinusitis, recurrent otitis media, and oti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Kocyigit 9 claims a female, while Khayat 10 documents a male predominance, consistent with our study. The main complaints in our study are also consistent with other similar studies [11][12][13][14] . The Otoscopic findings in our study i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Kocyigit 9 claims a female, while Khayat 10 documents a male predominance, consistent with our study. The main complaints in our study are also consistent with other similar studies [11][12][13][14] . The Otoscopic findings in our study i.e.…”
Section: Discussionsupporting
confidence: 93%
“…In some studies, age and gender-related changes were reported, while in other studies it was reported that age and gender did not change RFvalues. 10,11 In recent studies RF value of middle ear for healty children was reported between 650 to 1400 Hz. Ferekidis et al showed that mean RF value of the ears with acute otitis media on the day of the diagnosis was 380 Hz which increased 680 Hz on 10 th day and 749 Hz after 1 month period.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that children with adenoid hypertropy are more likely to have OME and beneficial effects of adenoidectomy on OME is also demonstrated. 10,11 The role of adenoid vegetation in OME is complex. Mechanical obstruction of the Eustachian tube with large adenoids is thought to be associated with OME, although small adenoids may also lead to OME by serving as reserve of pathogens causing tube edema and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Significant expenses, nonattendance of child from school, risk of anesthesia and other surgical procedure related morbidities have additionally featured the need of medicinal treatment for adenoid hypertrophy. Levels of serum immunoglobulins have been seen to be lower in patients who have experienced adenotonsillectomy than in healthy control group [4]. Also, AH may create fundamental irritation in kids and grown-ups as shows by an expansion in C-reactive protein and this is connected with psychological and cardiovascular morbidity which diminishes following adeno-tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%